2022
DOI: 10.1021/acsaem.2c02333
|View full text |Cite
|
Sign up to set email alerts
|

S-Doped NiII-Triazolate Derived Ni–S–C Catalyst for Electrochemical CO2 Reduction to CO

Abstract: Metal heteroatom doped carbon materials display remarkable catalytic performance in the electrochemical CO 2 reduction (ECR) because the doped heteroatoms can significantly change the local density of state and electronic structure of carbon, which induces charge polarization or structural defects. Herein, we synthesized S-doped Ni II -triazolate precursors with high purity and crystallinity through a simple one-step hydrothermal method. The high-temperature pyrolysis process produced a series of Ni−S−C T (T =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…7a). 25 Ni–S–C 1000 was revealed to exhibit the best CO 2 RR catalytic performance with 66.6% FE CO and good stability. The high temperature caused numerous defects and increased the pore volume.…”
Section: Mof-derived Transition Metal-based Catalystmentioning
confidence: 98%
See 1 more Smart Citation
“…7a). 25 Ni–S–C 1000 was revealed to exhibit the best CO 2 RR catalytic performance with 66.6% FE CO and good stability. The high temperature caused numerous defects and increased the pore volume.…”
Section: Mof-derived Transition Metal-based Catalystmentioning
confidence: 98%
“…The d-orbital of transition metals is filled with electrons close to the Fermi level, and the variability of the electron configuration of the d-orbital was reported to promote the desorption of intermediates and accelerate the reaction kinetics. 24,25 Meanwhile, porous carbon-based materials with unique characteristics are also considered favourable catalysts or support for electrocatalysis. 26 Metal-organic frameworks (MOFs) have been studied a lot in recent years due to the large surface area and tuneable structure by variation of the metal cation and organic linkers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, methane was the preferred product with the Fe/Ni nanoparticles, while hydrogen was the preferred product with pure greigite. Zhang et al studied the synthesis of Ni-S-C nanoparticles from S-doped Ni-triazolate starting material for the CO 2 reduction to CO [180]. The authors synthesized a pure Ni(II)-triazolate complex as a starting material followed by pyrolysis at three temperatures, 800, 900, and 1000 • C, which resulted in a Ni 3 S 2 material with carbon.…”
Section: Nis X -Based Nanomaterialsmentioning
confidence: 99%
“…More importantly, their study revealed that the transition‐metal, Ni atoms, played as CO 2 ECR active sites, whereas S atoms improved its electrocatalytic activity synergistically by comparing these two S‐doped and S‐free catalysts [18] . These electrocatalytic CO 2 reduction reactions could also be boosted acquired by using the powerful strategy of sulfur activation in Fe‐NS−C, [19] Ni−S−C T [20] and so on. Furthermore, the different central earth‐abundant transition‐metal atoms (Mn, Fe, Co, Ni, Cu, Sn⋅⋅⋅) have been explored for CO 2 reduction in numerous research groups to investigate the effect of central metal on catalytic activity and selectivity [21] .…”
Section: Introductionmentioning
confidence: 99%